Altering textural properties of fermented milk by using surface‐engineered Lactococcus lactis. Issue 4 (9th May 2018) - Tarazanova, Mariya; Huppertz, Thom; Kok, Jan; Bachmann, Herwig
Summary: Lactic acid bacteria are widely used for the fermentation of dairy products. While bacterial acidification rates, proteolytic activity and the production of exopolysaccharides are known to influence textural properties of fermented milk products, little is known about the role of the microbial surface on microbe–matrix interactions in dairy products. To investigate how alterations of the bacterial cell surface affect fermented milk properties, 25 isogenic Lactococcus lactis strains that differed with respect to surface charge, hydrophobicity, cell chaining, cell‐clumping, attachment to milk proteins, pili expression and EPS production were used to produce fermented milk. We show that overexpression of pili increases surface hydrophobicity of various strains from 3–19% to 94–99%. A profound effect of different cell surface properties was an altered spatial distribution of the cells in the fermented product. Aggregated cells tightly fill the cavities of the protein matrix, while chaining cells seem to be localized randomly. A positive correlation was found between pili overexpression and viscosity and gel hardness of fermented milk. Gel hardness also positively correlated with clumping of cells in the fermented milk. Viscosity of fermented milk was also higher when it was produced with cells with a chaining phenotype or with cells that overexpress exopolysaccharides. Our results show that alteration of cell surface morphology affects textural parameters of fermented milk and cell localization in the product. This is indicative of a cell surface‐dependent potential of bacterial cells as structure elements in fermented foods. Abstract : Microbe–matrix interactions in fermented foods are still poorly understood. We here investigated the effect of altering the lactococcal cell surface on textural properties of fermented milk. The results show that alteration of cell surface properties, such as the expression of pili, has profound effects on the viscosity and gel hardness of fermented milk.